A comparison of problems at the grassroots level in India identified by adults and children: Implications for Design and Technology Education - Datt, Sachin; Chunawala, Sugra (Design and Technology Education: An International Journal, 2018)
The focus of Design and Technology (D&T) education (Wilson & Harris, 2004) has been on designing and making activities and in developing technological capabilities amongst students. Innovation is an important aspect of D&T that helps in creating new products and artefacts to overcome the limitations of existing ones. Problem solving and problemidentification are inherent components of innovation and D&T education. This study aims to compare differences in problems identified by adults and children at the grassroots level in India. In particular, we ask what kind of differences are there in problems identified by adults and school students and what could be the reasons for the differences and itsimplications for design and technology education? The data of innovations was accessednfrom the website of the National Innovation Foundation (NIF), India. The innovators, both children and adults, had not received any design brief by an external agency and the range of problems identified by them were from diverse areas. We grouped the problem areasinto a number of categories. Contrary to conventional wisdom and literature about children being more creative than adults, we found a greater diversity in the problems tackled by adults. More importantly there were qualitative differences in the kind of problems identified by adults and children. Interestingly a category of problems that childrenidentified was related to human behaviour and students attempted to fix these behaviours through technology.